Electrolytic capacitor and method for manufacturing the same

By using sintered body electrode foil made of metal powder and controlling the viscosity of the electrolyte, the limitations of traditional electrochemical etching methods and environmental pollution problems are solved, and a high capacitance and stability of large electrostatic capacity capacitors are achieved.

JP7674602B2Active Publication Date: 2025-05-09RUBYCON CORPORATION +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024524844
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-02
Filing Date
2023-05-29
Publication Date
2025-05-09
Estimated Expiration
2043-05-29

AI Technical Summary

Technical Problem

When increasing the capacitance, existing electrolytic capacitors face the limitations of extended surface treatment, and traditional electrochemical etching methods have problems of environmental pollution and high economic costs.

Method used

The sintered body made of metal powder is used as the electrode foil. By adjusting the powder particle size and the thickness of the sintered body film, a sintered body electrode foil has a high characteristic surface area, and the viscosity of the electrolyte is controlled to 400 cP or less.

Benefits of technology

The unique large electrostatic capacity of the sintered body electrode foil is achieved, reducing environmental and economic burdens, and improving the durability of the capacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007674602000007
    Figure 0007674602000007
  • Figure 0007674602000008
    Figure 0007674602000008
  • Figure 0007674602000009
    Figure 0007674602000009
Patent Text Reader

Abstract

The present invention addresses the problem of providing: an electrolytic capacitor which employs, as an electrode foil, a sintered foil having a metal sintered body at least on the surface thereof, and which is capable of stably generating relatively large electrostatic capacitance unique to a sintered foil; and a method for producing said electrolytic capacitor. As a solution to the above problem, an electrolytic capacitor (1) according to the present invention is provided with: a capacitor element (2) comprising a positive electrode foil (8) in which a dielectric layer is formed, a negative electrode foil (9), and a separator (10) disposed between the positive electrode foil (8) and the negative electrode foil (9); and an electrolytic solution (3) with which the inside of the capacitor element (2) is impregnated. The positive electrode foil (8) or the negative electrode foil (9) is obtained by forming a sintered body of a composition that contains a metal powder into the shape of a foil (composed of a foil-like sintered body (8c)), or alternatively, by forming, on the surface of a base material, a sintered film (8b) composed of the sintered body. The viscosity μ [cP] of the electrolytic solution (3) at 25 [°C] is 400 [cP] or less.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrolytic capacitor and a method for manufacturing an electrolytic capacitor. [Background technology]

[0002] 2. Description of the Related Art There is known an electrolytic capacitor in which an electrolyte is impregnated in a capacitor element having a separator disposed between an anode foil and a cathode foil on which an oxide film or the like is formed as a dielectric layer.

[0003] Conventionally, in order to realize high capacitance in electrolytic capacitors, metal foils with an increased specific surface area by surface expansion are used for the electrode foil. Surface expansion is generally performed by forming a large number of pores on the surface of the metal foil by electrochemical etching (hereinafter, metal foils that have been etched may be referred to as "etched foils"). However, there is a limit to how much the specific surface area can be increased by etching, and it is becoming increasingly difficult to meet the increasing demand for high capacitance. In addition, etching has the disadvantages of using chemicals such as hydrochloric acid, which have a relatively large environmental and economic burden, and of electrochemically dissolving the metal foil, which may lead to a decrease in foil strength.

[0004] Taking these factors into consideration, Patent Document 1 (JP 2008-98279 A) describes a surface expansion method in which a composition containing metal powder (in this document, aluminum powder) is applied to the surface of a substrate (in this document, aluminum foil), and then heated and sintered to form a sintered film, thereby increasing the specific surface area (hereinafter, foil having a metal sintered body at least on its surface may be referred to as "sintered foil"). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2008-98279 A Summary of the Invention [Problem to be solved by the invention]

[0006] The sintered foil exemplified in Patent Document 1 can reduce environmental and economic burdens compared to conventional etched foils. In addition, it can prevent the foil strength from decreasing during the manufacturing process, and can achieve a relatively large capacitance by adjusting the particle size of the powder particles or sintered particles of the metal powder, the thickness of the sintered film, etc. However, depending on the properties of the electrolyte, the capacitance may not be stable and may not be fully exhibited. [Means for solving the problem]

[0007] The present invention has been made in consideration of the above circumstances, and aims to provide an electrolytic capacitor that uses a sintered foil having a metal sintered body at least on its surface as an electrode foil, and that can stably produce the relatively large electrostatic capacitance that is characteristic of sintered foil, and a manufacturing method thereof.

[0008] The present invention solves the above problems by the solution means described below as one embodiment.

[0009] The electrolytic capacitor according to the present invention is an electrolytic capacitor comprising: a capacitor element having an anode foil on which a dielectric layer is formed, a cathode foil, and a separator disposed between the anode foil and the cathode foil; and an electrolyte impregnated in the capacitor element, wherein the anode foil or the cathode foil is formed by forming a sintered body of a composition containing a metal powder into a foil shape, or a sintered body coating made of the sintered body is formed on the surface of a substrate, and the viscosity μ [cP] of the electrolyte at 25° C. is 400 cP or less. and the particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder is 5.0 μm or less (wherein the particle diameter D means the cumulative 50% median diameter in the volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope). It is characterized by:

[0010] Further, a method for producing an electrolytic capacitor according to the present invention is a method for producing an electrolytic capacitor comprising a capacitor element having an anode foil having a dielectric layer formed thereon, a cathode foil, and a separator disposed between the anode foil and the cathode foil, and an electrolyte impregnated in the capacitor element, wherein at least one of the anode foil and the cathode foil is formed by forming a sintered body of a composition containing a metal powder into a foil shape, or by forming a sintered body film made of the sintered body on the surface of a substrate, and adjusting the viscosity μ [cP] of the electrolyte at 25° C. to 400 cP or less. and adjusting the particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder to 5.0 μm or less (wherein the particle diameter D means the cumulative 50% median diameter in the volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope). It is characterized by:

[0011] According to this, the properties (viscosity μ) of the electrolyte are set to an appropriate state in relation to the sintered foil, so that the relatively large electrostatic capacitance specific to the sintered foil can be stably produced.

[0012] In addition, In the particle size distribution of the sintered grains, the particle size distribution on a volume basis is calculated from the particle size distribution on a number basis.

[0013] According to this, by increasing the specific surface area by fine sintered grains, a larger electrostatic capacitance can be realized, and such a large electrostatic capacitance can be stably produced.

[0014] In the electrolytic capacitor according to the present invention, it is more preferable that the viscosity μ [cP] of the electrolyte at 25° C. further satisfies the following formula (1): μ≦9.438D+227 (1)

[0015] In the method for producing an electrolytic capacitor according to the present invention, it is more preferable that the viscosity μ [cP] of the electrolyte at 25° C. is adjusted so as to further satisfy the following formula (1). μ≦9.438D+227 (1)

[0016] In the above formula (1), D means the particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder, and the particle diameter D means the cumulative 50% median diameter in the volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope. Note that, in the particle size distribution of the sintered grains, the volume-based particle size distribution is calculated from the number-based particle size distribution.

[0017] According to this, even if an electrolytic capacitor deteriorates over time (increase in viscosity μ) due to use, the large electrostatic capacitance specific to the sintered foil is hardly decreased and can be stably produced for a long period of time. Effect of the Invention

[0018] According to the present invention, in an electrolytic capacitor to which sintered foil is applied, it is possible to stably produce a relatively large electrostatic capacitance that is specific to sintered foil. [Brief description of the drawings]

[0019] [Figure 1] FIG. 1 is a schematic diagram (front cross-sectional view) showing an example of an electrolytic capacitor according to this embodiment. [Diagram 2] Fig. 2A is an explanatory diagram illustrating an example of a capacitor element in the electrolytic capacitor according to the present embodiment, and Fig. 2B is an explanatory diagram illustrating another example of a capacitor element in the electrolytic capacitor according to the embodiment of the present invention. [Diagram 3] Fig. 3 is an explanatory diagram illustrating an example of a method for manufacturing an electrolytic capacitor according to the present embodiment. Fig. 3A is an overall view of the capacitor element shown in Fig. 2A. Fig. 3B is a partial view showing a part of the capacitor element shown in Fig. 3A in more detail. [Figure 4] FIG. 4 is a graph of the capacitance appearance rate (A) in Table 1. [Diagram 5] Fig. 5A is a graph showing the change in capacitance appearance rate (C) when the viscosity increases by 10% in Table 2. Fig. 5B is a graph showing an approximation line to the scatter plot of Fig. 5A. [Figure 6] Fig. 6A is a graph showing an approximate straight line on a scatter diagram showing the relationship between the particle diameter D of the sintered grains (powder grains) of the sintered foil and the quasi-critical viscosity value. Fig. 6B is a graph showing an approximate straight line on a scatter diagram showing the relationship between the particle diameter D of the sintered grains (powder grains) of the sintered foil and the quasi-critical viscosity value. [Figure 7] 7A is a graph of the electrolyte retention amount in Table 3. FIG. 7B is a graph of the electrolyte retention rate versus the stable retention amount in Table 4. [Figure 8] Figure 8A is a graph of the capacitance from Table 5. Figure 8B is a graph of the capacitance reduction rate versus the stable capacitance from Table 6. [Figure 9] Fig. 9A is a graph in which the horizontal axis is plotted as the relational expression (1 / (Dμ2)) between the particle diameter D value and the viscosity μ value in Table 6, and the vertical axis is plotted as the reduction rate R corresponding to the D value and μ value, with both axes plotted in logarithmic scale. Fig. 9B is a graph showing the regression line calculated in Fig. 9A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] Hereinafter, the embodiment for carrying out the present invention will be described in detail with reference to the drawings. FIG. 1 is a schematic diagram (front cross-sectional view) showing an example of an electrolytic capacitor 1 according to the present embodiment. FIG. 2A is an explanatory diagram for explaining an example of a capacitor element 2 in the electrolytic capacitor 1 according to the present embodiment. FIG. 2B is an explanatory diagram for explaining another example of the capacitor element 2. Both FIG. 2A and FIG. 2B are schematic diagrams showing an example of the basic configuration of the capacitor element 2. Hereinafter, as an embodiment, a wound-type electrolytic capacitor 1 will be described as an example, but the present invention is not limited to this form, and may be, for example, a laminated type, a coin type, or the like. In addition, as an embodiment, an aluminum electrolytic capacitor 1 will be described as an example having an anode foil 8 made of an electrode material mainly made of aluminum or an aluminum alloy and having an oxide film 8d as a dielectric layer, but the present invention is not limited to this form, and may be, for example, a valve metal other than aluminum or its alloy.

[0021] As shown in FIG. 1, the electrolytic capacitor 1 according to this embodiment has a capacitor element 2 housed in an exterior material 6. The opening of the exterior material 6 is sealed with a sealing material 5, and the opening edge of the exterior material 6 is crimped and sealed to the sealing material 5. Lead terminals 4 (anode terminal 4a and cathode terminal 4b) are passed through two through holes provided in the sealing material 5, and lead wires 11 are drawn out to the outside of the electrolytic capacitor 1. The exterior material 6 is provided with an explosion-proof valve 7, which is a pressure valve as a safety valve, and is activated (opened) when the internal pressure of the electrolytic capacitor 1 reaches a certain level or higher, thereby releasing the gas in the electrolytic capacitor 1 and preventing explosion. The number and position of the explosion-proof valve 7 are not limited, and may be provided in the sealing material 5, or may be provided in both the exterior material 6 and the sealing material 5.

[0022] 2A, capacitor element 2 according to this embodiment includes an anode foil 8, a cathode foil 9, and a separator 10 disposed between the anode foil 8 and the cathode foil 9. An anode terminal 4a and a cathode terminal 4b are attached to the anode foil 8 and the cathode foil 9, respectively.

[0023] The electrode foils (anode foil 8 and cathode foil 9) are made of an electrode material whose main material is a valve metal such as aluminum or tantalum or an alloy thereof, and further have an optional base material 8a that supports the electrode material. The main material of the base material 8a is not particularly limited, but the base material 8a can also be a valve metal such as aluminum or tantalum or an alloy thereof. Note that the material is referred to as the "main material" here because it is acceptable for it to contain trace amounts of impurities, as described below.

[0024] The electrode material according to the present embodiment is mainly made of aluminum or an aluminum alloy. The aluminum in the aluminum or aluminum alloy preferably has a purity of 99.80 [mass%] or more from the viewpoint of preventing defects caused by impurities, and furthermore, the purity is preferably 99.99 [mass%] or more from the viewpoint of suppressing an increase in leakage current against a high temperature load. In addition, the aluminum alloy may be an alloy containing one or more of elements such as silicon, iron, copper, manganese, magnesium, chromium, zinc, titanium, vanadium, gallium, nickel, boron, and zirconium. In this case, the content of each of these elements is preferably 100 [ppm by mass] or less, particularly 50 [ppm by mass] or less.

[0025] In the electrode foils 8 and 9 according to this embodiment, the anode foil 8 is configured as a sintered foil, and the cathode foil 9 is configured as an etched foil, both of which have an expanded surface structure. The sintered foil of the anode foil 8 is a foil having a metal sintered body at least on its surface. On the other hand, the cathode foil 9 is configured, for example, by etching an aluminum foil, which is an electrode material, but the cathode foil 9 may also be configured as a sintered foil. The etching may be performed by DC electrolysis, AC electrolysis, or the like. For example, in DC electrolysis, the anode foil 8 is etched in a mixed aqueous solution of hydrochloric acid and sulfuric acid (hydrochloric acid: 1 mol / L, sulfuric acid: 3 mol / L) at 80°C with a DC current of 500 mA / cm. 2 ] for 1 min, then immersed in a nitric acid solution (nitric acid: 1 mol / L) at 75°C and subjected to a direct current of 100 mA / cm 2 ] for 5 [minutes] to perform the etching process.

[0026] In contrast, the sintered foil can be formed, for example, by applying a composition containing at least aluminum powder to the surface of an aluminum foil as the substrate 8a, and then heating and sintering the composition. As a result, as shown in FIG. 2A, a sintered foil can be formed in which a sintered film 8b made of a sintered body of a composition containing aluminum powder is formed on the surface of the aluminum foil. However, the sintered film 8b, which is an electrode material, only needs to be formed on at least one side of the aluminum foil as the substrate 8a that faces the cathode foil 9, and does not necessarily have to be formed on both sides of the aluminum foil as shown in FIG. 2A (i.e., the entire surface of the aluminum foil as shown in FIG. 3B). Therefore, the "surface of the substrate" in the claims may mean one side of the substrate 8a. In addition, the materials (main materials) of the substrate 8a and the sintered film 8b do not necessarily have to be the same. As an example, a sintered film 8b made of a sintered body of a composition containing aluminum alloy powder may be formed on the surface of the aluminum foil as the substrate 8a.

[0027] As another example, the sintered foil can be formed by a method in which a composition containing at least aluminum powder is heated and sintered without using the base material 8a, and then formed into a foil before and after the sintering. As a result, as shown in FIG. 2B, a sintered foil can be formed from a foil-shaped sintered body 8c in which a sintered body of a composition containing aluminum powder is formed into a foil shape.

[0028] As shown in FIG. 2A and FIG. 2B, the sintered body film 8b and the foil-shaped sintered body 8c are formed by sintering powder particles of aluminum or aluminum alloy powder while maintaining voids between them. That is, each sintered particle 8e is connected with voids to form a three-dimensional mesh structure, which is a porous sintered body. The sintered foil has an expanded surface structure with a specific surface area larger than that of an etched foil on its surface depending on the particle diameter D of the powder particles or sintered particles 8e, the thickness or porosity of the sintered body film 8b, etc. As a result, the electrolytic capacitor 1 according to this embodiment can achieve a large capacitance larger than that of an electrolytic capacitor to which an etched foil is applied. However, the sintered foil of FIG. 2A and FIG. 2B may be etched to further expand the surface.

[0029] For example, the smaller the particle diameter D of the powder grains of the aluminum powder or the sintered grains 8e of the aluminum powder, the larger the specific surface area and the larger the capacitance of the sintered foil. For this reason, the particle diameter D of the powder grains of the aluminum powder or the sintered grains 8e of the aluminum powder is preferably, for example, 5.0 μm or less, and more preferably 3.0 μm or less.

[0030] Here, the particle diameter D in the present application is a value in units [μm] defined as follows (the same in all descriptions of "particle diameter D" regardless of whether this definition is described or not). The particle diameter D [μm] of powder particles is the median diameter (D 50 The particle diameter D [μm] of the sintered grains 8e is the median diameter (D 50 )) of the sintered grains 8e observed, the diameter of which is measured as the particle size. However, the sintered grains 8e may be in a state where the sintered powder grains have melted and lost part of their shape, or the sintered powder grains may be in a state where they are partly connected to each other. In such cases, a portion having an approximately circular shape is approximately regarded as one sintered grain 8e, and its maximum diameter is measured as the particle size. Meanwhile, portions where it is difficult to distinguish the approximately circular shape are excluded. The particle sizes of a predetermined number of sintered grains 8e are measured, and the volume-based particle size distribution is calculated from the number-based particle size distribution of these. Then, the median diameter (D 50)) is obtained as the particle diameter D [μm] of the sintered grains 8e. The particle diameter D of the metal powder hardly changes before and after sintering, and the particle diameter D [μm] of the powder grains obtained by the above method is almost the same as the particle diameter D [μm] of the sintered grains 8e of the powder grains. In other words, the particle diameter D is specified as "particle diameter D of the powder grains of the metal powder or the sintered grains 8e of the metal powder" in this application because it is intended that the measurement of the particle diameter D may be performed using either the powder grains before sintering or the sintered grains 8e after sintering as a sample.

[0031] In forming the sintered foil, the composition containing aluminum or aluminum alloy powder may contain additives such as binders, solvents, sintering aids, and surfactants as necessary. These additives may be known or commercially available. For example, the binder may be a synthetic resin such as carboxy-modified polyolefin resin, vinyl chloride resin, vinyl acetate resin, vinyl chloride-vinyl acetate copolymer resin, vinyl alcohol resin, butyral resin, vinyl fluoride resin, acrylic resin, polyester resin, urethane resin, epoxy resin, urea resin, phenol resin, acrylonitrile resin, nitrocellulose resin, paraffin wax, or polyethylene wax, or a natural resin such as wax, tar (dry distillation liquid), glue, lacquer, rosin, or beeswax. For example, the solvent may be water or an organic solvent such as ethanol, toluene, ketones, or esters. Among these additives, for example, by adding a binder and / or a solvent, the composition containing aluminum or aluminum alloy powder has moldability and shape retention, and the sintered body film 8b and the foil-shaped sintered body 8c can be formed to an optimal thickness. By adjusting the type and content of these additives, the porosity of the sintered body film 8b and the foil-shaped sintered body 8c and the degree to which the additives remain can be adjusted. This allows the capacitance of the electrolytic capacitor 1 to be adjusted.

[0032] The sintering conditions of the composition are not limited, but as an example, the sintering temperature may be set to 560°C or higher and 660°C or lower for about 5 to 24 hours. The sintering atmosphere may be any of vacuum, an inert gas atmosphere such as argon gas, air atmosphere, an oxidizing atmosphere, a reducing atmosphere, etc. The pressure environment may be any of normal pressure, reduced pressure, and pressurized pressure.

[0033] Furthermore, when the composition contains organic additives such as organic binders, for example, it is advisable to heat the composition at 100°C to 600°C for 5 hours or more prior to sintering. This pretreatment (sometimes called "degreasing") and sintering process can evaporate the organic additives so that almost none remain.

[0034] An oxide film 8d is formed as a dielectric layer on the surface of the anode foil 8 configured as a sintered foil as described above by chemical conversion treatment. The chemical conversion treatment may be performed, for example, by anodizing treatment in which a voltage is applied while the target metal is immersed in a chemical conversion solution bath using the target metal as the anode to form the oxide film 8d, or may be performed by simply immersing the target metal in the chemical conversion solution bath. For example, the anodizing treatment is performed by applying a direct current of 10 mA / cm in a boric acid aqueous solution (boric acid: 0.01 mol / L or more and 5 mol / L or less) at a temperature of 30°C to 100°C. 2 ] or more 400[mA / cm 2 For example, the cathode foil 9 is treated at 1000 K for 5 minutes or more at 1000 K for 1 minute to form an oxide film 8d. In contrast, in the polar electrolytic capacitor 1 according to the present embodiment, the cathode foil 9 is not basically subjected to a chemical conversion treatment, but a natural oxide film (not shown) is formed on the surface of the cathode foil 9 by oxygen in the air.

[0035] The separator 10 disposed between the anode foil 8 and the cathode foil 9 to separate them is not particularly limited in configuration, and may be, for example, paper made of natural cellulose fibers such as Manila hemp pulp, or cloth, sheet, or film made of synthetic fibers such as nylon. Blends or spun products of natural and synthetic fibers may also be used. Note that, although FIG. 2 shows a schematic example of the basic configuration of the capacitor element 2 and shows one separator 10, the number of separators is not actually limited, and, for example, two separators (a first separator 10a and a second separator 10b) may be provided as shown in FIG. 3B.

[0036] The capacitor element 2 is impregnated with an electrolyte 3. The electrolyte 3 is contained in the gap between the electrode foils 8 and 9, and depending on the configuration and material of the separator 10, a portion of the electrolyte 3 may also be impregnated into the separator 10. The electrolyte 3 is in contact with the dielectric layer (oxide film 8d) formed on the anode foil 8, and is configured to function as a true cathode that essentially serves as the counter electrode of the anode foil 8. However, the electrolyte 3 does not need to completely fill the space between the electrode foils 8 and 9, and there may be an area between the electrode foils 8 and 9 that is not filled with the electrolyte 3, as long as the electrolyte 3 can perform this function.

[0037] The electrolyte 3 is a liquid component having fluidity. The electrolyte 3 contains a solvent and a solute, which is an electrolyte, and further contains a predetermined additive. The solvent may be a solvent consisting of only an organic solvent, or a water-organic solvent in which an organic solvent is used as the main solvent and a predetermined amount of water is added thereto. In addition, the water-organic solvent can increase the solubility of the electrolyte and the mobility of ions, thereby lowering the resistivity of the electrolyte 3. In addition, the freezing point of the solvent can be lowered, and electrical characteristics can be secured at a lower temperature. On the other hand, a solvent consisting of only an organic solvent can prevent the hydration reaction between the electrode foils 8 and 9 and water at high temperatures, thereby preventing an increase in the internal pressure of the capacitor element 2 due to the absence of water in the electrolyte 3.

[0038] Examples of organic solvents include protic solvents such as monohydric alcohols, such as methyl alcohol, ethyl alcohol, propyl alcohol, and butyl alcohol, dihydric alcohols, such as ethylene glycol, diethylene glycol, triethylene glycol, polyethylene glycol, and propylene glycol, and trihydric alcohols, such as glycerin, and derivatives thereof. Examples of aprotic solvents include lactone compounds, such as γ-butyrolactone, sulfolane, methylsulfolane, dimethylsulfolane, ethylene carbonate, propylene carbonate, pyrrolidine, 2-pyrrolidinone, N-methyl-2-pyrrolidinone, 1,3-dimethyl-2-imidazolidinone, tetrahydrofuran, acetonitrile, N-methylformamide, N,N-dimethylformamide, nitrobenzene, and derivatives thereof. Among these, one type may be used alone, or two or more types may be mixed and used. For example, a protic solvent and an aprotic solvent may be used together.

[0039] The solute, which is an electrolyte, may be an organic acid, an inorganic acid, a composite compound of an organic acid and an inorganic acid, or a derivative or a salt thereof. Of these, one kind may be used alone, or two or more kinds may be used in combination. For example, an organic acid and an inorganic acid may be used together.

[0040] Examples of organic acids and their derivatives include monocarboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, benzoic acid, caprylic acid, and their derivatives. Examples of dicarboxylic acids include oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, fumaric acid, maleic acid, phthalic acid, azelaic acid, sebacic acid, 1,6-decanedicarboxylic acid, 5,6-decanedicarboxylic acid, 1,10-decanedicarboxylic acid, and their derivatives. Examples of hydroxycarboxylic acids include citric acid, salicylic acid, and their derivatives. Examples of inorganic acids and their derivatives include phosphoric acid, boric acid, sulfamic acid, and their derivatives. In addition, examples of composite compounds of organic acids and inorganic acids and derivatives thereof include boron complexes of dicarboxylic acids or hydroxycarboxylic acids, and examples thereof include borodioxalic acid, borodimalonic acid, borodisuccinic acid, borodiadipic acid, borodimaleic acid, borodiphthalic acid, borodiglycolic acid, borodicitic acid, borodisalicylic acid, and derivatives thereof.

[0041] Furthermore, examples of salts of organic acids, inorganic acids, composite compounds of organic acids and inorganic acids, and derivatives thereof include ammonium salts, alkylammonium salts, amine salts, amidine salts, sodium salts, potassium salts, and the like.

[0042] The electrolyte may be added in an optimal amount according to the type, within a range in which the desired electrical conductivity can be secured and the electrolyte can be dissolved in the solvent. For example, an organic acid or its derivative or its salt may be added in a range of about 3 [mass %] to 30 [mass %] of the total mass of the electrolyte 3. An inorganic acid or its derivative or its salt may be added in a range of about 0.1 [mass %] to 15 [mass %] of the total mass of the electrolyte 3. In addition, when the organic acid component and the inorganic acid component are mixed and used, they may be added in a range of about 0.1 [mass %] to 15 [mass %] of the total mass of the electrolyte 3.

[0043] In addition to the solvent and solute, the electrolyte 3 may contain a predetermined additive as appropriate. These additives include substances that have the function of being a solvent or solute, but are usually added in relatively small amounts separately from the main solvent or main solute for the main purpose of achieving an effect due to other functions. Examples of additives include chelate compounds, sugars, gluconic acid, nitro compounds, etc.

[0044] Here, the viscosity μ of the electrolyte 3 according to this embodiment is set to 400 [cP] or less, more preferably 300 [cP]. Here, the viscosity μ in this application is the viscosity μ measured by a vibration viscometer at 25 [°C] for the electrolyte 3, and is expressed in units of [cP] (hereinafter, all descriptions of "viscosity μ" are the same regardless of whether this definition is described or not). By configuring the viscosity μ of the electrolyte 3 in an appropriate state in relation to the sintered foil, it is possible to stably produce a relatively large electrostatic capacitance specific to the sintered foil.

[0045] As described above, in the sintered foil, the smaller the particle diameter D of the powder grains of the aluminum powder or the sintered grains 8e, the larger the capacitance of the sintered foil, which is preferable. However, the smaller the particle diameter D, the more likely the capacitance becomes unstable in relation to the properties of the electrolyte 3. In contrast, in this embodiment, the viscosity μ of the electrolyte 3 is adjusted, so that the capacitance appears stably regardless of the size of the sintered grains 8e (i.e., even for sintered foils composed of relatively small sintered grains 8e). As a result, according to the example (Test 1) described later, for sintered foils with sintered grains 8e of, for example, 5.0 [μm] or 3.0 [μm], by setting the viscosity μ to 400 [cP] or less, the foil capacitance (capacitance of the foil) can be made to appear at a rate of appearance exceeding 80 [%]. In addition, by setting the viscosity μ to 300 [cP] or less, the foil capacitance (capacitance of the foil) can be made to appear at a rate of appearance exceeding 90 [%]. Therefore, in the sintered foil of this embodiment, the particle diameter D of the powder grains of the aluminum powder or its sintered grains 8e can be reduced to, for example, 5.0 μm or less, more preferably 3.0 μm or less, thereby making the capacitance sufficiently large and enabling such a large capacitance to be stably produced.

[0046] The viscosity μ of the electrolyte 3 can be adjusted to a desired value by adjusting the combination (e.g., selection of substances and adjustment of their mixing ratio) of the aforementioned electrolyte components (solvent components and solute components), concentrations, etc.

[0047] In addition, the fact that the viscosity μ of the electrolyte 3 is set to, for example, 400 [cP] or less means that the electrolyte 3 impregnated in the capacitor element 2 is set to the viscosity μ in the manufacturing process of the electrolytic capacitor 1. The viscosity μ of the electrolyte 3 may slightly decrease immediately after impregnation by absorbing moisture in the capacitor element 2, or may slightly increase over time as the moisture evaporates. However, even if such a possibility is taken into consideration, it is considered that the viscosity μ of the electrolyte 3 at the time of impregnation is almost the same as that at the time of impregnation in the electrolytic capacitor 1 completed through the subsequent manufacturing process if it is in an unused state. Therefore, for example, "the viscosity μ of the electrolyte 3 is set to 400 [cP] or less" can be defined as "the viscosity μ of the electrolyte 3 in the electrolytic capacitor 1 is 400 [cP] or less" as a synonymous configuration. It is also possible that the viscosity μ of the electrolyte 3 changes slightly when the viscosity μ of the electrolyte 3 is measured due to the volatilization of some components, but the change is very small and does not cause any problem.

[0048] On the other hand, as the electrolytic capacitor 1 is used, the viscosity μ of the electrolyte 3 increases due to the increased evaporation of water. As a result, the capacitance may decrease due to the imbalance between the properties (viscosity μ) of the electrolyte 3 and the structure (particle diameter D) of the sintered grains 8e. Therefore, in order to stabilize the capacitance against deterioration over time after use of the electrolytic capacitor 1, it is preferable that the viscosity μ of the electrolyte 3 be set more strictly as follows in relation to the particle diameter D of the powder grains of the aluminum powder or the sintered grains 8e thereof. That is, it is preferable that the viscosity μ of the electrolyte 3 at 25° C. satisfy the following inequality (1), and more preferably the following inequality (2). μ≦9.438D+227 (1) μ≦6.726D+162 (2)

[0049] However, D in the above inequalities (1) and (2) refers to the particle diameter D [μm] of the powder grains of the metal powder (here, aluminum powder) or the sintered grains 8e of the metal powder (here, the aluminum powder), and the particle diameter D refers to the cumulative 50[%] median diameter in the volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains 8e measured by observation with a scanning electron microscope. Note that, in the particle diameter distribution of the sintered grains 8e, the volume-based particle diameter distribution is calculated from the number-based particle diameter distribution.

[0050] According to the analysis of the embodiment (Test 1) described later, it was found that in the electrolytic capacitor 1 to which the sintered foil is applied, when the viscosity μ of the electrolyte 3 increases by a certain amount, there exists a lower viscosity region (stable region) where the capacitance hardly changes, and a higher viscosity region (unstable region) where the capacitance decreases relatively greatly, regardless of the size of the sintered grains 8e (powder grains). Therefore, the viscosity μ value of the boundary value between the stable region and the unstable region is defined as the "viscosity critical value", and the viscosity μ value of the region in the unstable region, which is close to the viscosity critical value and where the decrease in capacitance is relatively small, is defined as the "quasi-viscosity critical value". Specifically, the viscosity critical value is defined as the viscosity μ value when the change in the capacitance appearance rate is 0[%] based on the approximation line of the change in the capacitance appearance rate, and the quasi-viscosity critical value is defined as the viscosity μ value when the change is -1[%], where the change is allowed. By setting the viscosity μ of the electrolyte 3 to be below the viscosity critical value (inequality (2)) or below the quasi-critical viscosity value (inequality (1)), the capacitance can be maintained stably even when the electrolytic capacitor 1 deteriorates over time (increase in viscosity μ) due to use.

[0051] The above inequality (1) corresponds to a parameter that can set the viscosity μ of the electrolyte 3 to a quasi-critical viscosity value or less, and the above inequality (2) corresponds to a parameter that can set the viscosity μ of the electrolyte 3 to a quasi-critical viscosity value or less. The above inequality (1) and inequality (2) are inequalities based on an approximate straight line calculated by calculating the viscosity critical value and the quasi-critical viscosity value for each sintered foil composed of sintered grains 8e with different particle diameters D, and plotting the relationship between the particle diameter D [μm] and the viscosity critical value [cP] or the quasi-critical viscosity value [cP] on a graph. According to this, the target viscosity μ range of the electrolyte 3 becomes clear depending on the particle diameter D of the sintered grains 8e or powder grains that make up the sintered foil. By achieving this viscosity μ range, if the quasi-critical viscosity value (inequality (1)) is satisfied, the large capacitance specific to sintered foil can be stably produced for a long period of time without significant reduction even with deterioration over time (increase in viscosity μ) due to use of the electrolytic capacitor 1, and if the critical viscosity value (inequality (2)) is further satisfied, the capacitance can be stably produced for an even longer period of time. As a result, the life of the electrolytic capacitor 1 can be extended.

[0052] According to inequality (1), when the particle diameter D = 9.0 [μm], μ ≦ 312 [cP], when the particle diameter D = 5.0 [μm], μ ≦ 274 [cP], and when the particle diameter D = 3.0 [μm], μ ≦ 255 [cP]. According to inequality (2), when the particle diameter D = 9.0 [μm], μ ≦ 223 [cP], when the particle diameter D = 5.0 [μm], μ ≦ 196 [cP], and when the particle diameter D = 3.0 [μm], μ ≦ 182 [cP]. All of these satisfy the condition that the viscosity μ of the electrolyte 3 is 400 [cP] or less.

[0053] In this embodiment, there is no particular lower limit for the viscosity μ of the electrolytic solution 3. However, from the viewpoint of ensuring a certain degree of retention of the electrolytic solution 3 in the capacitor element 2, for example, the viscosity μ of the electrolytic solution 3 is preferably 2 [cP] or more, more preferably 10 [cP] or more, and even more preferably 30 [cP] or more.

[0054] In the electrolytic capacitor 1 according to the present embodiment having the above configuration, at least the anode foil 8 of the electrode foils 8 and 9 is configured as a sintered foil composed of sintered grains 8e having a predetermined particle diameter D, and the electrolyte 3 is configured to have a predetermined property, but other than these configurations, the basic production of the capacitor element 2 and the assembly of the electrolytic capacitor 1 can be performed in accordance with the conventional example. As an example, the wound electrolytic capacitor 1 according to the present embodiment is configured by sandwiching a separator 10 (first separator 10a and second separator 10b) between an anode foil 8 in which an oxide film 8d (not shown in FIG. 3B) has been formed by chemical conversion treatment and a lead terminal 4 (anode terminal 4a) is joined by crimping or the like to a sintered foil, and a cathode foil 9 in which a lead terminal 4 (cathode terminal 4b) is joined by crimping or the like to an etched foil, and then winding them together to form a substantially cylindrical shape as shown in FIG. 3A and FIG. 3B. The resulting wound body is subjected to another chemical conversion treatment as necessary, and then immersed in a tank of electrolyte 3 having the composition according to this embodiment to introduce (impregnate) electrolyte 3 into the gap between both electrode foils 8, 9, thereby producing capacitor element 2. Lead wire 11 is connected to lead terminal 4 at an appropriate time (lead terminal 4 and lead wire 11 are not shown in FIG. 3A). Introduction of electrolyte 3 may be performed under reduced pressure as necessary.

[0055] Next, the capacitor element 2 is housed in the exterior material 6, and the sealing material 5 is placed in the opening of the exterior material 6 to seal it. At this time, the lead terminals 4 (anode terminal 4a and cathode terminal 4b) are passed through and drawn out from two through holes provided in the sealing material 5. Next, the edge of the opening of the exterior material 6 is crimped to the sealing material 5 to seal it. In this way, the electrolytic capacitor 1 can be manufactured. Thereafter, if necessary, an aging treatment may be performed in which a voltage is applied for a predetermined time under high temperature conditions to repair any defects in the oxide film 8d that occurred when the foil was cut or wound. EXAMPLES

[0056] [Test 1] Sintered foils were produced by sintering aluminum powder with a powder grain diameter D of 3.0 μm, 5.0 μm, or 9.0 μm. Hereinafter, sintered foils made of 3.0 μm sintered grains (powder grains) will be referred to as "3.0 μm foil," sintered foils made of 5.0 μm sintered grains (powder grains) as "5.0 μm foil," and sintered foils made of 9.0 μm sintered grains (powder grains) as "9.0 μm foil." The powder grain diameter D is the cumulative 50% median diameter in the volume-based particle size distribution measured by the laser diffraction / scattering method.

[0057] First, 60 parts by mass of aluminum powder having each particle size D and 40 parts by mass of acrylic binder were mixed and dispersed in toluene, and the coating liquid was applied to both sides of an aluminum foil using an applicator to form a film, and then dried. Next, the aluminum foil was heated in an argon gas atmosphere at 655°C for 7 hours to be sintered. Next, assuming application to electrolytic capacitors for medium and high voltages with a rated voltage of 400V or 450V or more, the sintered foil was subjected to a predetermined anodizing treatment to form an oxide film with a film withstand voltage of 650V or more.

[0058] After that, the test pieces were cut to the specified dimensions in accordance with the JEITA standard EIAJ RC-2364A "Test Method for Electrode Foil for Aluminum Electrolytic Capacitor" (revised March 1999) (https: / / www.jeita.or.jp / japanese / standard / book / RC-2364A / #target / page_no=1) established by the Japan Electronics and Information Technology Industries Association (formerly the Electronic Industries Association of Japan).

[0059] The sintered foil thus produced for evaluation was subjected to the measurement of the foil capacitance (capacitance) [μF / cm2] at 120 [Hz], the frequency range in which electrolytic capacitors are commonly used, in accordance with the description of the above-mentioned standard (EIAJ RC-2364A), using an aqueous solution of ammonium pentaborate as the measurement solution (1), which corresponds to the measurement solution "C" for capacitance of medium- and high-voltage anodic formed foil (voltage category: rated dielectric strength voltage 170 [V] or more). 2 After washing and drying the foil, the foil capacitance (electrostatic capacitance) at 120 [Hz] [μF / cm ] was measured in the same manner as above, using as measurement solution (2) each electrolyte solution containing the prescribed components adjusted to each viscosity μ shown in Table 1 in place of measurement solution (1). 2 The viscosity μ was measured in cP in an electrolyte solution at 25°C using a vibration viscometer, as described above. Specifically, a vibration viscometer (product name: Viscomate VM-1A) manufactured by Sekonic Corporation was used. The foil capacitance [μF / cm 2 ] is the unit area (1 cm ) calculated from the measured foil capacitance value [μF] 2 ) foil capacitance value [μF / cm 2 ].

[0060] The foil capacitance value in the measurement solution (2) [μF / cm 2 ] is the foil capacitance value in the measurement solution (1) [μF / cm 2 ] was divided by this to calculate the capacitance appearance rate (A). Capacitance appearance rate (A) = foil capacitance value in test solution (2) [μF / cm 2 ] / foil capacitance value in measurement solution (1) [μF / cm 2 ]

[0061] The capacitance appearance rate (A) indicates the stability (or instability) of the capacitance in relation to the properties (viscosity μ) of the electrolyte in the sintered foil, and the closer the value is to 1 (100% when converted into a percentage), the more stable the capacitance is. The capacitance appearance rate (A) is converted into a percentage and shown in Table 1 and Figure 4 (note that the (A) value [%] in Table 1 is rounded off to one decimal place).

[0062] [Table 1]

[0063] As shown in Table 1, the smaller the particle diameter D of the sintered grains (powder grains), the larger the capacitance of the sintered foil. On the other hand, as shown in Table 1 and Figure 4, when the viscosity μ of the electrolyte is high, the capacitance appearance rate (A) is low. For example, when the viscosity μ is 670 [cP], it was 67.7 [%] for 3.0 [μm] foil, 74.5 [%] for 5.0 [μm] foil, and 78.0 [%] for 9.0 [μm] foil. From this, it can be seen that the smaller the particle diameter D of the sintered grains (powder grains), the more likely the capacitance is to become unstable in relation to the viscosity μ of the electrolyte. On the other hand, when the viscosity μ of the electrolyte is set to a low value below a certain level, the capacitance appearance rate (A) was close to 100 [%], regardless of the particle diameter D of the sintered grains (powder grains), and the capacitance appeared stably. Specifically, when the viscosity μ of the electrolyte was 400 cP or less, the capacitance decrease was reliably kept to less than -20% (the capacitance appearance rate (A) exceeded 80%), and when the viscosity μ of the electrolyte was 300 cP or less, the capacitance decrease was kept to less than -10% (the capacitance appearance rate (A) exceeded 90%).

[0064] Therefore, in an electrolytic capacitor using sintered foil, it is preferable that the viscosity μ of the electrolyte is 400 [cP] or less, more preferably 300 [cP] or less, since the foil capacitance can be stably generated. Furthermore, it is more preferable that the particle diameter D of the sintered grains (powder grains) is 5.0 [μm] or less, more preferably 3.0 [μm] or less, since the foil capacitance itself can be improved to realize a larger electrostatic capacitance and the capacitance can be stably generated.

[0065] Next, the differential coefficient of the volume appearance rate (A) value at each viscosity μ value was calculated as the volume appearance rate change (B) per unit viscosity (1 cP). The following formula for second-order accuracy differential with unequal intervals was applied to calculate the differential coefficient. f'(x i )=(s 2 f i+1 +(t 2 -s 2 )f i -t 2 fi-1 ) / st(s+t) f i ≡f(x i ) t ≡ (x i+1 -x i ) s ≡ (x i -x i-1 )

[0066] Next, to evaluate the change in capacity appearance rate (C) when the viscosity μ of the electrolyte increases by a certain amount, an increase of 10% was assumed as an arbitrary amount of fluctuation (amount of increase), and the change in capacity appearance rate (C) when the viscosity increases by 10% was calculated by multiplying the change in capacity appearance rate (B) per unit viscosity (the differential coefficient of the capacity appearance rate (A)) by the viscosity fluctuation rate (here, 10% of each viscosity μ value) according to the following formula. Change in volume appearance rate when viscosity increases by 10% (C) = "Change in volume appearance rate per unit viscosity (B) (differential coefficient of volume appearance rate (A))" x (viscosity μ value x 0.1)

[0067] The change in capacitance appearance rate (C) when the viscosity increases by 10% is converted to a percentage and shown in Table 2 and FIG. 5A (note that the (C) values ​​(%) in Table 2 are rounded to the second decimal place).

[0068] [Table 2]

[0069] As shown in Table 2 and Figure 5A, it can be seen that the change in capacitance appearance rate (C) has a viscosity μ region (stable region) where the capacitance hardly changes and a viscosity μ region (unstable region) where the capacitance drops relatively significantly, regardless of the particle diameter D of the sintered grains (powder grains), that is, for sintered foils made of sintered grains of any particle diameter D. Furthermore, it can be seen from Figure 5A that the boundary value between the stable region and the unstable region (referred to as the "critical viscosity value") is approximately around 200 [cP].

[0070] Therefore, for the four points of 280 [cP], 340 [cP], 540 [cP] and 600 [cP] in the unstable region, the approximate straight line equations for 3.0 [μm] foil, 5.0 [μm] foil and 9.0 [μm] foil were calculated by the least squares method. The approximate straight line equations were calculated by calculating the vertical axis intercept and horizontal axis intersection point of each approximate straight line equation f (x), g (x) and h (x) as a solution that minimizes the sum of the squared residuals of the three sintered foils. At this time, the value of the vertical axis intercept was considered to be the same value for all approximate straight line equations, and a constraint condition was applied. Figure 5B is a graph showing the calculated approximate straight line on the scatter diagram of Figure 5A.

[0071] The calculated vertical axis intercept value was 2.48% (rounded to the second decimal place). The horizontal axis intersection values ​​were 182.6cP for the 3.0μm foil, 195.1cP for the 5.0μm foil, and 222.7cP for the 9.0μm foil (rounded to the second decimal place). These horizontal axis intersection points represent the viscosity μ value [cP] when the capacitance appearance rate change (C) is 0% on the approximation line, and this was defined as the aforementioned "critical viscosity value." Furthermore, the viscosity μ value [cP] when the capacitance appearance rate change (C) is -1% on the approximation line was calculated and defined as the "quasi-critical viscosity value." The quasi-critical viscosity values ​​were 256.2 cP for the 3.0 μm foil, 273.8 cP for the 5.0 μm foil, and 312.5 cP for the 9.0 μm foil (each rounded to the first decimal place).

[0072] The quasi-critical viscosity value of each sintered foil thus obtained was plotted on a graph in relation to the particle diameter D [μm] of each sintered grain (powder grain), and the following approximate linear equation (1) was obtained by the least squares method. The graph is shown in Figure 6A. y=9.4383x+227.35 (1) ≒9.438x+227

[0073] The critical viscosity values ​​of each sintered foil obtained in this way were also plotted on a graph in relation to the particle diameter D [μm] of each sintered grain (powder grain), and the following approximate linear equation (2) was obtained by the least squares method. The graph is shown in Figure 6B. y=6.7263x+162.03 (2) ≒6.726x+162

[0074] As described above, the viscosity critical value represents the viscosity μ value at the boundary between the viscosity μ region (stable region) where the capacitance hardly changes when the viscosity μ increases by a certain amount and the viscosity μ region (unstable region) where the capacitance decreases relatively greatly, and is defined as the viscosity μ value when the capacitance appearance rate change (C) is 0 [%] on the approximation line. On the other hand, the quasi-viscosity critical value is defined as the viscosity μ value when the capacitance appearance rate change (C) is -1 [%], which is acceptable, on the approximation line, and represents the viscosity μ value in the unstable region but near the viscosity critical value and where the decrease in capacitance is relatively small.

[0075] Therefore, in an electrolytic capacitor to which sintered foil is applied, the viscosity μ [cP] of the electrolyte is set to a state (i.e., below the quasi-critical viscosity value) that satisfies the inequality (1) "μ≦9.438D+227" with the particle diameter D of the sintered grains (powder grains) as a variable based on the approximate linear formula (1), so that the viscosity μ is set close to the critical viscosity value or in a stable region. As a result, even if the viscosity μ increases over time due to the evaporation of moisture as the electrolytic capacitor is used, the large capacitance specific to the sintered foil can be stably generated for a long period of time without almost any decrease, and the life of the electrolytic capacitor can be extended. Furthermore, the viscosity μ [cP] of the electrolyte is set to a state (i.e., below the critical viscosity value) that satisfies the inequality (2) "μ≦6.726D+162" with the particle diameter D of the sintered grains (powder grains) as a variable based on the approximate linear formula (2), so that the viscosity μ is reliably set in a stable region. As a result, the capacitance can be stably generated for a longer period of time, and the life characteristics can be further improved.

[0076] Furthermore, if the theoretical minimum value of the viscosity μ in inequality (1) and inequality (2) is D=0, then "μ≦227" is derived from inequality (1) and "μ≦162" is derived from inequality (2). From this, if the viscosity μ of the electrolyte is at least 227 [cP] or less, and more preferably at least 162 [cP] or less, the stability of the capacitance can be ensured against an increase in a given viscosity μ of the electrolyte, regardless of the particle diameter D of the sintered grains (powder grains).

[0077] In determining whether the above inequality is satisfied, the particle diameter D [μm] value is substituted with a value up to one decimal place (if measured to two decimal places or less, round off to the first decimal place). Also, the viscosity μ value [cP] is calculated as an integer value by rounding off the first decimal place of the solution.

[0078] [Test 2] As mentioned above, in the present invention, the lower limit of the viscosity μ of the electrolyte is not particularly set, but the lower limit of the viscosity μ was examined as a more preferred embodiment of the invention. 3.0 [μm] foil, 5.0 [μm] foil, and 9.0 [μm] foil were prepared by the same method as in Test 1. That is, 60 [parts by mass] of aluminum powder having each particle size D and 40 [parts by mass] of acrylic binder were mixed and dispersed in toluene, and the coating liquid was applied to both sides of the aluminum foil having a thickness of 30 [μm] using an applicator to form a film and dried. Next, this aluminum foil was degreased in an air atmosphere at 200 [℃] to 450 [℃] for 5 [hours], and then heated and sintered in an argon gas atmosphere at 655 [℃] for 7 [hours]. In this way, an aluminum sintered foil having a total thickness of 130 [μm] was manufactured by forming a sintered body film of 50 [μm] on both sides of a base material having a thickness of 30 [μm]. Next, an oxide film having a withstand voltage of 650 [V] or more was formed on the sintered foil in the same manner as in Test 1. After that, each sintered foil was cut into a test piece having a dimension of 17 [mm] × 50 [mm] as an evaluation sintered foil, and the weight of each (weight A) was measured.

[0079] Next, the sintered foil was impregnated with the electrolyte by immersing it in each electrolyte solution consisting of predetermined components adjusted to each viscosity μ shown in Table 3. Next, the sintered foil taken out of the electrolyte solution was centrifuged at 1000 [rpm] for 5 [minutes] to perform a deliquification process, and the weight (weight B) immediately after the deliquification process was measured. Then, the weight increase [mg] obtained by subtracting weight A [mg] from weight B [mg] was calculated as the electrolyte retention amount [mg] of the sintered foil. As described above, the viscosity μ is the viscosity μ [cP] measured in the electrolyte solution at 25 [℃] using a vibration type viscometer. Specifically, a vibration type viscometer (product name: Viscomate VM-1A) manufactured by Sekonic Co., Ltd. was used. The electrolyte retention amount of the sintered foil is shown in Table 3 and FIG. 7A.

[0080] [Table 3]

[0081] As shown in Table 3 and FIG. 7A, regardless of the particle diameter D of the sintered grains (powder grains), that is, in the sintered foil composed of sintered grains of any particle diameter D, in the low viscosity region where the viscosity μ of the electrolyte is, for example, below 50 [cP], when the viscosity μ drops extremely, the electrolyte retention amount gradually drops. In other words, from the viewpoint of ensuring the retention in the electrode foil, that is, the constant retention of the electrolyte in the capacitor element in which the sintered foil is applied to the electrode foil, it is preferable that the electrolyte has a certain viscosity μ or more. On the other hand, as shown in Table 3 and FIG. 7A, in the sintered foil composed of sintered grains of any particle diameter D, in the low viscosity region where the viscosity μ of the electrolyte is, for example, below 50 [cP], when the extremely low viscosity μ increases, the electrolyte retention amount gradually increases and converges to a predetermined retention amount, entering a stable region where it hardly changes. Therefore, in order to verify the lower limit of the suitable viscosity μ based on the viewpoint of the stability of the electrolyte retention amount, the stable retention amounts were set as 31 [mg] as an example of the electrolyte retention amount in the stable region of the 3.0 [μm] foil used in this test, 40 [mg] as an example of the electrolyte retention amount in the stable region of the 5.0 [μm] foil, and 42 [mg] as an example of the electrolyte retention amount in the stable region of the 9.0 [μm] foil, and each measured value in Table 3 was converted into a retention rate [%] relative to the stable retention amount (retention rate: 100 [%]). The results are shown in Table 4 and Figure 7B.

[0082] [Table 4]

[0083] Specifically, the retention rates [%] in Table 4 and FIG. 7B represent values ​​calculated using the following formula (rounded off to two decimal places). Retention rate [%] = (electrolyte retention amount [mg] at target particle size D (sintered foil) and target viscosity μ (electrolyte) / stable retention amount [mg] at target particle size D (sintered foil)) x 100 For example, the retention rate [%] of 3.0 [μm] foil at 1.3 [cP] is: Retention rate [%]=(5.2 / 31)×100=16.77

[0084] As shown in Table 4 and FIG. 7B, in the sintered foil composed of sintered grains of any particle diameter D, when the viscosity μ of the electrolyte is 2 [cP] or more, a relatively stable electrolyte retention rate of more than 50 [%] is ensured. Moreover, when the viscosity μ of the electrolyte is 10 [cP] or more, an even more stable electrolyte retention rate of more than 85 [%] is ensured. Therefore, it can be said that if the viscosity μ of the electrolyte is, for example, 30 [cP] or more, an extremely stable electrolyte retention rate can be ensured. This shows that in an electrolytic capacitor to which a sintered foil is applied, from the viewpoint of ensuring a certain electrolyte retention rate for the capacitor element, the viscosity μ of the electrolyte is preferably 2 [cP] or more, more preferably 10 [cP] or more, and even more preferably 30 [cP] or more.

[0085] [Test 3] As described above, in the present invention, the lower limit of the viscosity μ of the electrolyte is not particularly set, but as a more preferred embodiment of the invention, the lower limit of the viscosity μ was examined from another perspective. 3.0 [μm] foil, 5.0 [μm] foil, and 9.0 [μm] foil were prepared by the same method as in Test 1 and Test 2. That is, using aluminum powder having each particle diameter D, a sintered aluminum foil having a total thickness of 130 [μm] was manufactured by forming a sintered body film of 50 [μm] on each side of a base material having a thickness of 30 [μm], and then an oxide film having a film withstand voltage of 650 [V] or more was formed on the sintered foil. In addition, an aluminum etched foil for a cathode foil having a thickness of 20 [μm] was also prepared.

[0086] Next, of the prepared electrode foils, the sintered foil was used as the anode foil and the etched foil was used as the cathode foil, and the sintered foil was wound as a capacitor element. Next, the capacitor element was impregnated with a chemical conversion solution containing boric acid at a concentration of 4% and a voltage of up to 470 [V] was applied between the anode foil and the cathode foil to perform a re-chemical conversion treatment. Next, the capacitor element was cleaned by repeatedly performing a vacuum impregnation treatment with a predetermined cleaning solution and a deliquification treatment by centrifugation. Next, the capacitor element was washed by repeatedly performing a vacuum impregnation treatment with an electrolyte and a deliquification treatment by centrifugation. After that, the capacitor element was impregnated with each electrolyte composed of the predetermined components adjusted to each viscosity μ shown in Table 5 by performing a vacuum impregnation treatment with an electrolyte. Next, the capacitor element was subjected to a deliquification treatment by centrifuging at 1000 [rpm] for 3 [seconds], and then housed in an exterior material, and a sealant was placed on the opening of the exterior material to seal it. The wound electrolytic capacitor thus manufactured was measured for its high-frequency capacitance at 100 kHz, which is higher than the frequency commonly used for electrolytic capacitors, to evaluate its compatibility with high frequencies and its compatibility with high-level EMI (Electro Magnetic Interference) countermeasures. As mentioned above, the viscosity μ is the viscosity μ [cP] measured with an electrolytic solution at 25°C using a vibration viscometer. Specifically, a vibration viscometer (product name: Viscomate VM-1A) manufactured by Sekonic Corporation was used. The high-frequency capacitance of the electrolytic capacitor to which the evaluation sintered foil was applied is shown in Table 5 and FIG. 8A.

[0087] [Table 5]

[0088] As shown in Table 5 and Figure 8A, regardless of the particle diameter D of the sintered grains (powder grains), that is, in the sintered foil composed of sintered grains of any particle diameter D, in the low viscosity region where the viscosity μ of the electrolyte is, for example, below 50 [cP], the capacitance gradually decreases when the viscosity μ becomes extremely low. On the other hand, as shown in Table 5 and Figure 8A, in the sintered foil composed of sintered grains of any particle diameter D, in the low viscosity region where the viscosity μ of the electrolyte is, for example, below 50 [cP], when the extremely low viscosity μ increases, the capacitance gradually increases and converges to a predetermined capacitance, entering a stable region where it hardly changes. Therefore, the stable capacitances were set to 19.17 [μF] as an example of the capacitance in the stable region of the 3.0 [μm] foil used in this test, 18.16 [μF] as an example of the capacitance in the stable region of the 5.0 [μm] foil, and 13.91 [μF] as an example of the capacitance in the stable region of the 9.0 [μm] foil, and each measured value in Table 5 was converted into a reduction rate R for the stable capacitance (ratio: 1). The results are shown in Table 6 and Figure 8B.

[0089] [Table 6]

[0090] Specifically, the reduction rate R in Table 6 and FIG. 8B represents a value calculated by the following formula (rounded off to the fifth decimal place). Reduction rate R = 1 - (Capacitance [μF] at target particle size D (sintered foil) and target viscosity μ (electrolyte) / Stable capacitance [μF] at target particle size D (sintered foil)) For example, the reduction rate R of 3.0 μm foil at 1.3 cP is: Reduction rate R=1-(12.37 / 19.17)=0.3547 It is also possible to grasp the reduction rate R in [%] units by multiplying the reduction rate R calculated by the above formula by 100. Hereinafter, for ease of understanding, the reduction rate R may be expressed in [%] units.

[0091] As shown in Table 6 and FIG. 8B, even at the lowest viscosity μ of 1.3 [cP], the reduction rate R for the 3.0 [μm] foil is 35.47 [%], the reduction rate R for the 5.0 [μm] foil is 16.80 [%], and the reduction rate R for the 9.0 [μm] foil is 10.35 [%]. That is, in the sintered foil composed of sintered grains of any particle diameter D, the reduction rate R remains at about 35 [%] or less, and the capacitance is relatively stable overall even in the low viscosity region. Therefore, this result does not necessarily require the setting of a lower limit of the viscosity μ of the electrolyte in the present invention. On the other hand, from the viewpoint of ensuring a more sufficient and stable capacitance in a low viscosity region where the viscosity μ is, for example, below 50 [cP] in a usage environment where a high level of EMI countermeasures is required, it is preferable that the electrolyte has a viscosity μ of a certain level or more.

[0092] Therefore, in order to verify the preferable lower limit of the viscosity μ based on this viewpoint, the relationship between each particle diameter D value and the viscosity μ value: (1 / (Dμ 2 The values ​​of D and μ were plotted on the horizontal axis, and the values ​​of the reduction rate R corresponding to the D and μ values ​​were plotted on the vertical axis, with both axes plotted on a logarithmic scale. The results are shown in Figure 9A. For example, the rightmost plot in FIG. 9A is a plot of the reduction rate R at 1.3 cP for a 3.0 μm foil, and the horizontal axis value is (1 / (Dμ 2 ))=1 / (3.0×(1.3) 2 )=0.1972, and the value on the vertical axis is 0.3547.

[0093] As shown in FIG. 9A, regardless of the particle diameter D of the sintered grains (powder grains), that is, regardless of the sintered foil composed of sintered grains of any particle diameter D, the distribution of the reduction rate R almost overlaps a line with a slope of 1, and the relationship between the value of the particle diameter D and the value of the viscosity μ is: (1 / (particle diameter D × viscosity μ 2 ) ) is roughly proportional to the regression equation: R = A / (Dμ 2 ) and take the logarithm of both sides: logR=log( A / (Dμ 2) )" and estimate the proportional constant A using the least squares method. Then, the objective function: "S = Σ[logR i -log( A / (D i μ i 2 ) )] 2 The value of A that minimizes (where symbol i is a variable from 1 to N and symbol N is the number of data) is A = (Π(R i D i μ i 2 ) 1 / N " and the estimated proportionality constant A is "(reduction rate R × particle diameter D × viscosity μ 2 It can be calculated as the geometric mean of R = A / (Dμ 2 )" is transformed into "A=RDμ 2 " Based on this, (RDμ 2 ) is used as the estimated value of the proportionality constant A. Similarly, the estimated value of the proportionality constant A is calculated by the following equation: (reduction rate R × particle diameter D × viscosity μ 2 ) geometric mean. When the geometric mean is actually calculated, the estimated value of the proportionality constant A is calculated as 1.552 (rounded off to the fourth decimal place).

[0094] As a result, the regression equation is: R = A / (Dμ 2 ) is expressed by the following equation (3). R = 1.552 / (Dμ 2 ) ···(3) FIG. 9B shows the regression line calculated for the distribution of the reduction rate R shown in FIG. 9A: R=1.552 / (Dμ 2 )" (Eq. (3)) is superimposed on the graph.

[0095] According to equation (3), for example, the inequality: "1.552 / (Dμ 2 If the particle diameter D and viscosity μ satisfy the inequality "1.552 / (Dμ)≦0.5", the reduction rate R relative to the stable capacity is suppressed to about 0.5 (about 50[%]) or less. 2If the particle diameter D and viscosity μ satisfy the inequality "1.552 / (Dμ)≦0.35", the reduction rate R relative to the stable capacity is suppressed to about 0.35 (about 35[%]) or less. 2 If the particle diameter D and viscosity μ satisfy the inequality "1.552 / (Dμ)≦0.1", the reduction rate R relative to the stable capacity is suppressed to about 0.1 (about 10[%]) or less. 2 If the particle diameter D and viscosity μ satisfy the inequality "1.552 / (Dμ)≦0.05", the reduction rate R relative to the stable capacity is suppressed to about 0.05 (about 5[%]) or less. 2 If the particle diameter D and viscosity μ satisfy the condition "0.01")≦0.01", the reduction rate R relative to the stable capacity can be suppressed to approximately 0.01 (approximately 1%]) or less.

[0096] From the above, in terms of securing sufficient and stable capacitance in a low viscosity region where the viscosity μ is below 50 [cP] in a usage environment where a high level of EMI countermeasures is required, the inequality: "1.552 / (Dμ 2 It is preferable to satisfy the inequality: "1.552 / (Dμ 2 It is more preferable to satisfy the inequality: "1.552 / (Dμ 2 It is more preferable to satisfy the inequality: "1.552 / (Dμ 2 It is more preferable that the inequality: "1.552 / (Dμ 2 It is more preferable that the above-mentioned parameter satisfies "≦0.01". Note that, in an electrolytic capacitor using sintered foil, this parameter is particularly effective for setting the particle diameter D of the sintered grains (powder grains) and the viscosity μ of the electrolyte when assuming a relatively high frequency operating environment, for example, 10 kHz to 100 kHz.

Claims

1. a capacitor element including an anode foil having a dielectric layer formed thereon, a cathode foil, and a separator disposed between the anode foil and the cathode foil; an electrolytic capacitor comprising: an electrolyte impregnated in the capacitor element, The anode foil or the cathode foil is formed by forming a sintered body of a composition containing a metal powder into a foil shape, or by forming a sintered body coating made of the sintered body on the surface of a substrate, The viscosity μ [cP] of the electrolyte at 25° C. is 400 cP or less; The particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder is 5.0 μm or less (wherein the particle diameter D means the cumulative 50% median diameter in the volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope). An electrolytic capacitor characterized by:

2. The viscosity μ [cP] of the electrolyte at 25° C. further satisfies the following formula (1):

2. The electrolytic capacitor according to claim 1 . μ≦9.438D+227...(1) (Here, D means a particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder, and the particle diameter D means a cumulative 50% median diameter in a volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope.)

3. A capacitor element including: an anode foil having a dielectric layer formed thereon; a cathode foil; and a separator disposed between the anode foil and the cathode foil; and an electrolytic solution impregnated in the capacitor element, At least one of the anode foil and the cathode foil is formed by forming a sintered body of a composition containing a metal powder into a foil shape, or by forming a sintered body coating made of the sintered body on a surface of a substrate; The viscosity μ [cP] of the electrolyte at 25° C. is adjusted to 400 cP or less, The particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder is adjusted to 5.0 μm or less (wherein the particle diameter D means the cumulative 50% median diameter in the volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope). A method for manufacturing an electrolytic capacitor comprising the steps of:

4. The viscosity μ [cP] of the electrolyte at 25° C. is further adjusted to satisfy the following formula (1). The method for producing an electrolytic capacitor according to claim 3, μ≦9.438D+227...(1) (Here, D means a particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder, and the particle diameter D means a cumulative 50% median diameter in a volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope.)

5. The viscosity μ [cP] of the electrolyte at 25° C. further satisfies the following formula (1):

2. The electrolytic capacitor according to claim 1 . μ≦9.438D+227...(1) (Here, D means a particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder, and the particle diameter D means a cumulative 50% median diameter in a volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope.)

6. The viscosity μ [cP] of the electrolyte at 25° C. further satisfies the following formula (2):

2. The electrolytic capacitor according to claim 1 . μ≦6.726D+162 (2) (Here, D means a particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder, and the particle diameter D means a cumulative 50% median diameter in a volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope.)

7. When the viscosity μ [cP] of the electrolyte at 25° C. is 50 cP or less, the following formula (3) is further satisfied:

2. The electrolytic capacitor according to claim 1 . 1.552 / (Dμ 2 )≦0.5 ・・・(3) (Here, D means a particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder, and the particle diameter D means a cumulative 50% median diameter in a volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope.)

8. When the viscosity μ [cP] of the electrolyte at 25° C. is 50 cP or less, the following formula (3) is satisfied in addition to the formula (1):

3. The electrolytic capacitor according to claim 2 . 1.552 / (Dμ 2 )≦0.5 ・・・(3) (Here, D means a particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder, and the particle diameter D means a cumulative 50% median diameter in a volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope.)

9. When the viscosity μ [cP] of the electrolyte at 25° C. is 50 cP or less, the following formula (3) is satisfied in addition to the formula (1):

6. The electrolytic capacitor according to claim 5 . 1.552 / (Dμ 2 )≦0.5 ・・・(3) (Here, D means a particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder, and the particle diameter D means a cumulative 50% median diameter in a volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope.)

10. When the viscosity μ [cP] of the electrolyte at 25° C. is 50 cP or less, the following formula (3) is satisfied in addition to the formula (2):

7. The electrolytic capacitor according to claim 6, 1.552 / (Dμ 2 )≦0.5 ・・・(3) (Here, D means a particle diameter D [μm] of the powder grains of the metal powder or the sintered grains of the metal powder, and the particle diameter D means a cumulative 50% median diameter in a volume-based particle diameter distribution of the powder grains measured by a laser diffraction / scattering method or the sintered grains measured by observation with a scanning electron microscope.)

11. The viscosity μ [cP] of the electrolyte at 25° C. is 2 cP or more.

11. The electrolytic capacitor according to claim 1, 2, 5, 6, 7, 8, 9, or 10, characterized in that

12. The viscosity μ [cP] of the electrolyte at 25° C. is 10 cP or more.

11. The electrolytic capacitor according to claim 1, 2, 5, 6, 7, 8, 9, or 10, characterized in that

13. The viscosity μ [cP] of the electrolyte at 25° C. is 30 cP or more.

11. The electrolytic capacitor according to claim 1, 2, 5, 6, 7, 8, 9, or 10, characterized in that

Citation Information

Patent Citations

  • Electrode foil for electrolytic capacitor

    JP1993275286A

  • Electrolytic capacitor and electrolytic solution for driving the same

    JP2005303062A

  • Electrode material for aluminum electrolytic capacitor, and its manufacturing method

    JP2008098279A

  • Solid electrolytic capacitor and method for manufacturing the same

    JP2018110233A

  • Conductive electrolyte system with viscosity reducing co-solvents

    US6744619B1